Importance of Time Spent Standing for Those at Risk of Diabetic Foot Ulceration - Najafi, Bijan (American Diabetes Association, 2010)
OBJECTIVE: Despite the high cumulative plantar stress associated with standing, previous physical activity reports of diabetic patients at risk of foot ulceration have not taken this activity into account. This study aimed to monitor spontaneous daily physical activity in diabetic peripheral neuropathy (DPN) patients and examine both walking and standing activities as important foot-loading conditions. RESEARCH DESIGN AND METHODS: Thirteen DPN patients were asked to wear a body-worn sensor for 48 h. Body postures (sitting, standing, and lying) and locomotion (walking, number of steps, and postural transition) were extracted. RESULTS: Patients daily spent twice as much time standing (13 ± 5%) as walking (6 ± 3%). They spent 37 ± 6% of time sitting and 44 ± 8% lying down. The average number of steps per day was 7,754 ± 4,087, and the number of walking episodes was 357 ± 167 with maximum duration of 3.9 ± 3.8 min. CONCLUSIONS: The large portion of DPN patients' time spent standing with the feet loaded requires further consideration when treating and preventing foot ulcers.